2006
DOI: 10.1002/adfm.200500549
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Synthesis of Amino Acid Polyoxometalate Nanotubes by One-Step Solid-State Chemical Reaction at Room Temperature

Abstract: A novel and convenient method—solid‐state chemical reaction at room temperature—is reported for the synthesis of amino acid polyoxometalate nanotubes. As a convenient synthesis method for nanomaterials, it may open up a new pathway for the fabrication of organic–inorganic hybrid materials with nanotubular structure. Here, three novel tyrosine (Tyr) polyoxometalate nanotubes, (HTyr)3PMo12O40 · 3H2O, (HTyr)3PW12O40 · 3H2O, and (HTyr)4SiW12O40 · 5H2O are successfully synthesized via a one‐step solid‐state chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
35
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(38 citation statements)
references
References 30 publications
2
35
0
Order By: Relevance
“…[13] Jia and co-workers synthesized three novel tyrosine (Tyr) POM NTs by solid-state chemical reactions. [14] Wang prepared Zn 1.2 H 0.6 PW 12 O 40 NTs by using cellulose fibers as templates. [15] We obtained K 4 SiW 12 O 40 microtubes by a template-free method in an aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…[13] Jia and co-workers synthesized three novel tyrosine (Tyr) POM NTs by solid-state chemical reactions. [14] Wang prepared Zn 1.2 H 0.6 PW 12 O 40 NTs by using cellulose fibers as templates. [15] We obtained K 4 SiW 12 O 40 microtubes by a template-free method in an aqueous solution.…”
Section: Introductionmentioning
confidence: 99%
“…[ 27] This confirmed that the majority of Pc enters was located in Keggin ions supported on SBA-15. [28] The peak in the spectrum of H 3 PO 4 -SBA-15 at 0.8 ppm could be assigned to molecular H 3 PO 4 .I nt he spectrumo fa ctivated H 3 PO 4 -SBA-15, four pronounced peaks can be seen at chemical shifts of 0.8, À10.8, À22.8, and À35.9 ppm. Zhang and coworkers reported similar results for SiO 2 impregnated with H 3 PO 4.…”
mentioning
confidence: 97%
“…Particularly, low-temperature solid-state route has been found to be a simple, efficient way and shows specific advantages, such as convenience, economical, less energy and material consumption and high yield [5][6][7][8] .…”
mentioning
confidence: 99%